2021
DOI: 10.1139/cjm-2020-0484
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal mechanisms of lavender essential oil in the inhibition of rot disease caused by Monilinia fructicola in postharvest flat peaches

Abstract: As a natural antimicrobial agent, lavender essential oil (LEO) is generally recognized to be safe and effective in the inhibition of phytopathogenic fungi. Direct contact and fumigation (in vivo and in vitro) were used to study the fungistatic effect of LEO on Monilinia fructicola. Additionally, the effect on the ultrastructure of cells and degree of destruction of the cell membrane of M. fructicola were revealed. In addition, the effects of LEO on the expression levels of particular apoptosis-related genes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…They ascribed this low inhibitory activity to the slow release of volatiles from the liposomes (Xu et al, 2022). Xiong et al (2021) reported a relevant inhibitory activity of lavender EO on M. fructicola, both in direct contact and with fumigation. These authors associated the antifungal effects of Lavandula sp.…”
Section: Discussionmentioning
confidence: 99%
“…They ascribed this low inhibitory activity to the slow release of volatiles from the liposomes (Xu et al, 2022). Xiong et al (2021) reported a relevant inhibitory activity of lavender EO on M. fructicola, both in direct contact and with fumigation. These authors associated the antifungal effects of Lavandula sp.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study did not consider the possible adverse effects of high concentrations of essential oils on the peach quality and safety. Essential oils may cause phytotoxicity, oxidative damage, or allergic reactions in some cases (De Corato et al, 2010;Elshafie et al, 2015b;Fontana et al, 2021;Taheri et al, 2021;Xiong et al, 2021;Cao et al, 2022;Lin et al, 2022). Therefore, it is important to evaluate the optimal concentration and application method of essential oils that can balance between antifungal efficacy and peach quality and safety.…”
Section: Effect Of Essentials Oils Against B Cinereamentioning
confidence: 99%
“…The minimum growth was controlled at 25% concentration in Early Grand and the maximum growth was controlled at 100% concentration in Shah Pasand. This implies that there is a variation in the sensitivity of different peach cultivars to essential oil treatment and that different concentrations of essential oils are required for different cultivars (Fontana et al, 2021;Mou et al, 2021;Oliveira Filho et al, 2021;Xiong et al, 2021;Cao et al, 2022). It may be related to the genetic, physiological, or morphological characteristics of different peach cultivars or to the environmental conditions under which they were grown (De Corato et al, 2010;Carovic-Stanko et al, 2013;Oliveira Filho et al, 2021;Taheri et al, 2021;Yan et al, 2021;Cao et al, 2022;Lin et al, 2022).…”
Section: Effect Of Essentials Oils Against B Cinereamentioning
confidence: 99%
“…Xiong et al . 21 reported a complete fungal inhibition for Lavender EO at 800 μL/L against Monilinia fructicola. Their study indicated that the utilized antagonistic mechanisms included destruction of the cell membrane, cytoplasmic leakage, and induction of cell apoptosis.…”
Section: Introductionmentioning
confidence: 98%